Dinamika Komunikasi Politik dalam Proses Formulasi Peraturan Daerah Tentang Fasilitasi Penyelenggaraan Pesantren Kota Lubuk Linggau - Muhammad Agus Kurniawan; Suratman Suratman; Jatmiko Yogopriyatno (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This research analyzes the dynamics of political communication in the formulation of the Regional Regulation on the Implementation of Islamic Boarding Schools in Lubuk Linggau City. Using a descriptive qualitative method, this research utilizes interviews, observations, and document analysis involving members of the DPRD. Using Kingdon's Multiple Streams Framework, this study reveals that the regulation emerged through the convergence of three main streams: the problem stream, which highlights the limited access of pesantren to funding and legal protection; the policy stream, which is reflected in the legislative initiative of Commission IV of the DPRD supported by national regulations and academic partnerships; and the political stream, which involves political support from local parties and support from the executive. These converging streams open a policy window that allows pesantren issues to enter the formal policy agenda. The findings underscore that effective political communication, cross-sectoral collaboration, and strategic framing of pesantren as socio-educational institutions are crucial in advancing local regulations. This research offers practical insights for other regions that want to develop contextualized faith-based regulations. Future research is recommended to examine policy implementation outcomes and comparative analysis across different jurisdictions to assess policy transferability and long-term impact.